Cleft Surgery at Ship Hospital in Remote Island: Reflections and Experiences - Fakhriah Safirah; Mohammed Avicenna; Jeremy Nicolas Sibarani; Kezia Eveline; Alki Andana; Lobredia Zarasade; Agus Harianto (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2026)
Introduction: Cleft lip with or without cleft palate requires timely surgical management to optimize feeding, speech development, and facial growth. In archipelagic regions, geographic isolation and limited healthcare infrastructure may delay access to specialized cleft care. Hospital ship–based outreach programs have emerged as an alternative strategy to deliver surgical services to underserved island communities. This report presents a descriptive case series of cleft lip repairs performed during a hospital ship mission in remote islands of South Sulawesi, Indonesia. Case Presentation: Two patients with untreated cleft lip deformities were identified during surgical screening conducted as part of a hospital ship outreach mission. Both presented in adolescence or adulthood after prolonged delays in accessing definitive treatment. Cleft lip repair using a modified Millard rotation–advancement technique was performed under general anesthesia. Early postoperative outcomes were assessed based on surgical complications and scar evaluation. Postoperative follow-up was limited to 7 days. Conclusion: Hospital ship–based cleft lip repair may represent a feasible approach to delivering surgical care in remote island settings. However, evidence remains limited to early postoperative outcomes, and further studies with larger cohorts and standardized long-term follow-up are needed to evaluate functional and aesthetic results.